KAJIAN PEMANFAATAN POMPA AIR BANTUAN PEMERINTAH UNTUK MENUNJANG IRIGASI PERTANIAN DI KABUPATEN - Vilian F. Tumober; Leo H. Kalesaran; David P. Rumambi (COCOS, 2023)
AbstactThis research was conducted to determine the feasibility of using pumps infulfilling water for plants so that the farming system. Support for groundwaterirrigation by using pumps for farming activities in Minahasa Regency. Based onthe description above, research will be carried out on "Studies on the use ofgovernment-assisted water pumps to support agricultural irrigation in MinahasaRegency". The results showed that the most water pump assistance was providedin 2018 in Tombariri District, and the least in 2020 in Langowan and KakasDistricts were all donated to farmer groups. The pump assistance provided by thegovernment to farmer groups is the TWP 150 type of water pump, in reality in thefield the types of water pumps provided by the government are all the same,namely the Tanikaya TWP 150 water pump type with gasoline. Interview dataobtained from farmer groups receiving water pump assistance indicated that thereare two sources of water at the pump location, namely rivers and springs. Theresults of a survey conducted showed that the pump placement locations of allthose distributed were not placed in a certain place or no one used pump houses,because their use was carried out on a rotating basis so that the pumps wereplaced according to the needs in the field. The results obtained were that the useof government-assisted water pumps was not optimized properly because most ofthe assistance was not used properly or was rarely used, with the reason thatrainfall was insufficient and there were also pumps provided by the governmentthat the pump components were not complete, there were also pumps that hadbeen provided. switch to another tool.Keywords : Water pump, irrigation, utilization